Zika Virus Outbreak on Curaçao and Bonaire, a Report Based on Laboratory Diagnostics Data - Lim, Stephanie M.; Wever, Robert; Pas, Suzan D.; Bonofacio, Gygliola; Koopmans, Marion P. G.; Martina, Byron E. E. (Frontiers in Public Health, 2019)
Background Zika virus (ZIKV) emerged in May 2015 in Brazil, from which it spread to many other countries in Latin America. Cases of ZIKV infection were eventually also reported in Curaçao (January 2016) and Bonaire (February 2016). Methods In the period of 16 December 2015 until 26 April 2017, serum, EDTA-plasma or urine samples were taken at Medical Laboratory Services (MLS) from patients on Curaçao and tested in qRT-PCR at the Erasmus Medical Centre (EMC) in the Netherlands. Between 17 October 2016 until 26 April 2017 all samples of suspected ZIKV-patients collected on Curaçao, as well as on Bonaire, were tested at MLS. Paired urine and/or serum samples from patients were analyzed for ZIKV shedding kinetics, and compared in terms of sensitivity for ZIKV RNA detection. Furthermore, the age and gender of patients were used to determine ZIKV incidence rates, and their geozone location to determine the spatial distribution of ZIKV cases. Results In total, 781 patients of 2820 tested individuals were found qRT-PCR-positive for ZIKV on Curaçao. The first two ZIKV cases were diagnosed in December 2015. A total of 112 patients of 382 individuals tested qRT-PCR-positive for ZIKV on Bonaire. For both islands, the peak number of absolute cases occurred in November 2016, with 247 qRT-PCR confirmed cases on Curaçao and 66 qRT-PCR-positive cases on Bonaire. Overall, a higher proportion of women than men was diagnosed with ZIKV on both islands, as well as mostly individuals in the age category of 25-54 years old. Furthermore, ZIKV cases were mostly clustered in the east of the island, in Willemstad. Conclusions ZIKV cases confirmed by qRT-PCR indicate that the virus was circulating on Curaçao between at least December 2015 and March 2017, and on Bonaire between at least October 2016 and February 2017, with peak cases occurring in November 2016. The lack of preparedness of Curaçao for the ZIKV outbreak was compensated by shipping all samples to the EMC for diagnostic testing; however, both islands will need to put the right infrastructure in place to enable a rapid response to an outbreak of any new emergent virus in the future.